Comparative views and the prospects for transatlantic cooperation : German resources in African studies - Bergenthum, Hartmut (2006)
The paper presents an overview about some of the international relevant projects of digital resources in Germany. Online presentations of primary sources, e.g. photographic material, and bibliographic tools supporting research, such as cross searching, will be presented as potential partners of resource sharing with North America. Not only the possibility of cooperation will be sketched, but also necessary preliminary work and some obstacles will be outlined. This report is accompanied by a short characterization of African studies in Germany and the status quo of Open Access-initiatives.